Nghiên cứu tổng hợp spinel niken nhôm trên nền oxit silic - Ngà, Nguyễn Kim; Chi, Đặng Kim (Vietnam Journal of Chemistry, 2014)
Nickel aluminates spinel NiAl2O4 in the silica glassy matrix was prepared through insitu sol-gel reaction. The influence of temperature and the molar ratio of metals to Si on the formation of the spinel were investigated. The DTA, TGA and XRD analyses showed that NiAl2O4/SiO2 was completely produced at 800oC. The surface properties of the synthesized spinel were identified by nitrogen adsorption-desorption method.